A facile hydrolysis–solvolysis procedure for conjugated bile acid sulfates - G P van Berge-Henegouwen (Journal of Lipid Research, 1977)
Methods for hydrolyzing and solvolyzing conjugated bile acid sulfates were compared on reference mixtures of conjugated and unconjugated bile acid sulfates gas–liquid chromatography to assess recovery, and thin-layer chromatography and zonal scanning to define the products occurring after hydrolysis. Conventional methods in which solvolysis preceded vigorous alkaline saponification gave incomplete recoveries. However, essentially complete recovery of primary and secondary bile acid sulfates was obtained with a mild alkaline saponification procedure followed by acidification and extraction into ether, in shich complete solvolysis was shown to occur within 12 hours. Based on these findings, we developed and validated a simple hydrolysis–solvolysis procedure; the method features mild alkaline hydrolysis, acidification to pH 1, and extraction with ether followed by a 1-hour incubation.